The establishment of a telestroke service using multimodal CT imaging decision assistance: "Turning on the fog lights". (March 2017) - Demeestere, Jelle; Sewell, Claire; Rudd, Jennifer; Ang, Timothy; Jordan, Louise; Wills, James; Garcia-Esperon, Carlos; Miteff, Ferdinand; Krishnamurthy, Venkatesh; Spratt, Neil; Lin, Longting; Bivard, Andrew; et al.
Highlights: The implementation and experience of a telestroke service using multimodal CT imaging is proposed. Using multimodal CT imaging is in line with the paradigm shift seen in modern stroke care. The addition of multimodal CT imaging does not seem to pose a risk for patient safety. The addition of multimodal CT imaging leads to increased detection of stroke mimics. The addition of CT angiography may lead to increased detection of intracranial vessel occlusions. Abstract: Telestroke services have been shown to increase stroke therapy access in rural areas. The implementation of advanced CT imaging for patient assessment may improve patient selection and detection of stroke mimics in conjunction with telestroke. We implemented a telestroke service supported by multimodal CT imaging in a rural hospital in Australia. Over 21 months we conducted an evaluation of service activation, thrombolysis rates and use of multimodal imaging to assess the feasibility of the service. Rates of symptomatic intracranial haemorrhage and 90-day modified Rankin Score were used as safety outcomes. Fifty-eight patients were assessed using telestroke, of which 41 were regarded to be acute ischemic strokes and 17 to be stroke mimics on clinical grounds. Of the 41 acute stroke patients, 22 patients were deemed eligible for thrombolysis. Using multimodal CT imaging, 8 more patients were excluded from treatment because of lack of treatment target. Multimodal imaging failed to be obtained in one patient. For the 14 treated patients, median door-imaging time was 38 min. Median door-treatment time was 91 min. A 90-day mRS ⩽2 was achieved in 40% of treated patients. We conclude that a telestroke service using advanced CT imaging for therapy decision assistance can be successfully implemented in regional Australia and can be used to guide acute stroke treatment decision-making and improve access to thrombolytic therapy. Efficiency and safety is comparable to established telestroke services.